Female Genital Tract Congenital Malformations : Classification, Diagnosis and Management - Grimbizis, Grigoris F.; Campo, Rudi; Gordts, Stephan; Tarlatzis, Basil C (Springer London : Imprint: Springer, 2015)
Using the new ESHRE/ESGE classification system, this book presents all uterine, cervical and vaginal anomalies in a systematic way. The diagnostic work-up of women with female genital malformations is reviewed in an evidence-based fashion, taking into account the availability of new non-invasive diagnostic methods. The treatment strategies and the therapeutic alternatives to restore health are also critically reviewed.   Female Genital Tract Congenital Malformations: Classification, Diagnosis and Management assesses all the latest information concerning the pathogenesis, diagnosis and treatment of female genital malformations. It is a vital manual for all trainees and practitioners within the fields of obstetrics and gynecology, radiologists, researchers in the field of human reproduction, fertility specialists, endoscopists, and ultrasonographers
Keywords: Diagnosis, Ultrasonic; Endoscopic surgery; Gynecology; Interventional radiology; Medicine; Reproductive Medicine; Surgery